2019
DOI: 10.1248/cpb.c18-01029
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms for Protection of Hepatocytes against Bile Salt Cytotoxicity

Abstract: Biliary lipids consist mainly of bile salts, phospholipids and cholesterol, which form mixed micelles and vesicles. Bile salts play various physiological roles but have damaging effects on cell membranes due to their detergent properties. The cytotoxicity of bile salts on hepatocytes leads to liver injuries and is largely determined by the bile salt species, the concentrations of bile salts, phospholipids and cholesterol, and the lipid composition of cell membranes. In bile, monomers and simple micelles of bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 77 publications
(169 reference statements)
1
14
0
Order By: Relevance
“…It was previously shown that treatment of high fat diet-fed mice with the ASBTi for 16 weeks shifted the hepatic bile acid composition shifted toward a more hydrophobic and thus potentially cytotoxic profile (10). In vitro studies have shown that PC protects hepatocytes from bile acid-induced cytotoxicity (48,49). Although not injurious when hepatic PC synthesis is intact, the ASBTi-induced shift to a more hydrophobic bile acid pool may be injurious under PC-deficient conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that treatment of high fat diet-fed mice with the ASBTi for 16 weeks shifted the hepatic bile acid composition shifted toward a more hydrophobic and thus potentially cytotoxic profile (10). In vitro studies have shown that PC protects hepatocytes from bile acid-induced cytotoxicity (48,49). Although not injurious when hepatic PC synthesis is intact, the ASBTi-induced shift to a more hydrophobic bile acid pool may be injurious under PC-deficient conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Bile salts damage cell membranes due to their detergent properties. The biliary phospholipids are necessary to protect hepatocytes from bile salt cytotoxicity [8,40]. The cytotoxicity of bile salts is attenuated by the formation of mixed micelles with phospholipids.…”
Section: Biliary Mixed Micellesmentioning
confidence: 99%
“…The cytotoxicity of bile salts is attenuated by the formation of mixed micelles with phospholipids. PC is the predominant (>95%) biliary phospholipid, whereas only small amounts of PE, PS, and SM are present in bile [8,41]. The phospholipid secretion from hepatocytes into bile is mediated by the transporter ABCB4 [41][42][43][44].…”
Section: Biliary Mixed Micellesmentioning
confidence: 99%
See 2 more Smart Citations